Pengendalian Persediaan Guna Meningkatkan Efesiensi Biaya Produksi Pada CV. Buala di Idanogawo - Lombu, Yanto; Mendrofa, Martha Surya Dinata; Bate’e, Maria Magdalena; Waruwu, Suka’aro (LPPM Universitas HKBP Nommensen, 2024)
Companies basically have to carry out appropriate inventory management to anticipate situations or challenges in order to achieve the ultimate goal of minimizing expenditure costs. Companies must plan the supply of raw materials to avoid shortages or running out of stock. By having inventory, it is hoped that the company can carry out the production process according to needs so that the costs required are lighter and more effective. Apart from that, having sufficient supplies of materials is also expected to facilitate production activities or services to company consumers and avoid shortages of raw materials. Inventory shortages can be detrimental to the company in this case increased financing. This research uses an exploratory type of quantitative research. The research sample is the entire population, namely 3 people, namely 1 (one) Director, 1 (one) Manager, 1 (one) Manager, so this research is a population research. The research results show that good inventory control can support sustainability initiatives. By reducing excess inventory, companies can reduce the environmental impact of production. The cause of the lack of material supplies at CV. Buala is when there is rainfall for days on end so that no raw materials are transported and processed, so the supply of materials runs out of stock. To anticipate material stock shortages, CV. Buala attempts to control inventory using the lead time method. Lead time is a time lag that occurs between the time an order is placed until the goods enter the warehouse. If the Lead Time is long, the Reorder Point must be placed earlier so that stock does not run out before the new shipment arrives